Syed Nazim Ali and Umar A. Oseni (Eds.), Waqf Development and Innovation: Socio-Economic and Legal Perspectives, London and New York: Routledge, 2022, 302 p. - Saqib Hafiz Khateeb (Turkish Journal of Islamic Economics)
This is a review of Waqf Development and Innovation: Socio-Economic and Legal Perspectives, edited by Syed Nazim Ali and Umar A. Oseni.